On the interaction between deprotonated Cytosine (C‐H) and Ba2+: Infrared multiphoton spectroscopy and dynamics - Cruz Ortiz, Andres Felipe (2020)
Gas-phase interactions between Ba2+ and deprotonated cytosine (C(−H)) were studied in [C(−H)Ba]+ and [C(−H)BaC]+ complexes by IRMPD spectroscopy coupled to tandem mass-spectrometry in combination with DFT calculations. For the [C(−H)BaC]+ complex only one [C(−H)KAN1O−Ba-Canti]+ isomer was found, although the presence of another structure cannot be excluded. This isomer features a central tetracoordinated Ba2+ that simultaneously interacts with keto-amino [C(−H)]− deprotonated on N1 and neutral keto-amino C. Both moieties are in different planes as a consequence of an additional NH…O=C hydrogen bond between C and [C(−H)]−. A sequential IRMPD dynamics is observed in this complex. For the [C(−H)Ba]+ complex produced by electrospray ionization two isomers ([C(−H)KAN1OBa]+ and [C(−H)KAN3OBa]+) were identified, in which Ba2+ interacts simultaneously with the C=O group and the N1 or N3 atom of the keto-amino [C(−H)]−, respectively. A comparison with the related [C(−H)Pb]+ complex (J. Y. Salpin et al., Chem. Phys. Chem. 2014, 15, 2959–2971) is also presented.